Achieving Net Zero Emissions Target: Development of Carbon Dioxide Handling Technologies, Its Challenges and Barriers - Mahidin; Maulana, Farid; Mukramah; Adisalamun; Hisbullah; Hadi, Abdul; MH, Nurdin; Abnisa, Faisal (Eksergi, 2025)
Abatement of carbon emission to net zero level in 2050 is a serious work for Indonesia in all sectors. In this article, review on the current status of CC technologies was conducted including commercial scale and R&D works. The technologies performance was also inserted in order to provide the information that valuable and useful in technological selection. However, the challenges and barriers for Indonesia in their efforts to reduce carbon emissions are not only about technological aspects; the issues of policy, socio culture, law and human resources also play an important role. In order to ensure the project going well, regulations and policies are needed both at the national and provincial levels, besides the massive socialization efforts from various stakeholders.